A construção amorosa ao longo dos tempos : sobre os caminhos da ternura e da sexualidade - Ferreira Junior, Antonio Gonçalves (2013)
This study seeks, through Freudian psychoanalysis, called to discuss the construction loving (Enriquez, 2003) in contemporary consumer society. More specifically, it aims to analyze this construction based on loving their instinctual roots tied to current tender and sensual that according to Freud (1996/1905) is the fundamental basis of the love life of individuals, finding the dynamics of repression the guidance of their expressions. Therefore we conducted a survey of the concept of love in Freudian theory, especially in its relation to the current tender and sensual lovemaking, among other important components of this manifestation as repression and the unconscious. Moreover, with the help of discussions Lejarraga (2002) on the topic, deepen the discussion about the importance of the ego instincts and sexual instincts as important foundations for the developments of the two currents of lovemaking. Then, in view of the influence of repression on the dynamics between current tender and sensual, come a brief historical journey from antiquity to contemporary society, pointing out the influence that rules and traditions play in setting different constructs representations of love. Considering mainly the intense mediation of culture on the links between individuals and their impact on lovemaking. We understand that in accordance with the standards and traditions in different historical paths of the two currents of lovemaking are important characteristics in its expression. This phenomenon is possible because each social underpinning certain ideal construction used up loving the prohibitions and waivers prior to engender new possibilities in the libidinal economy of individuals. More specifically in contemporary consumer society under the aegis of the culture industry repressions are mediated through dictates as no permanence, no accumulation and not binding. These points hinder the confluence of two streams of love life and move to the secondary narcissism, as important elements to building a building that loving otherness, sublimation and mentoring are the exponents.